2021
DOI: 10.7554/elife.63972
|View full text |Cite
|
Sign up to set email alerts
|

HP1α is a chromatin crosslinker that controls nuclear and mitotic chromosome mechanics

Abstract: Chromatin, which consists of DNA and associated proteins, contains genetic information and is a mechanical component of the nucleus. Heterochromatic histone methylation controls nucleus and chromosome stiffness, but the contribution of heterochromatin protein HP1α (CBX5) is unknown. We used a novel HP1α auxin-inducible degron human cell line to rapidly degrade HP1α. Degradation did not alter transcription, local chromatin compaction, or histone methylation, but did decrease chromatin stiffness. Single-nucleus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 120 publications
(250 reference statements)
3
96
1
Order By: Relevance
“…There is emerging evidence that histone post-translational modifications influence the mechanical properties of the nucleus and that cells modulate their epigenetic state to adapt to changes in applied stress. Using an auxin-inducible degron system to deplete cellular CBX5/HP1α, Strom et al [ 158 , 159 ] found that loss of CBX5/HP1α results in significant nuclear softening but not the loss of heterochromatin domains, consistent with their persistence when the methyltransferases responsible for synthesizing H3K9me3 are knocked out [ 160 ]. HP1 can dimerize and potentially cross-link chromatin fibers together [ 161 ].…”
Section: Solid and Liquid States Of Chromatin In The Nucleusmentioning
confidence: 99%
See 1 more Smart Citation
“…There is emerging evidence that histone post-translational modifications influence the mechanical properties of the nucleus and that cells modulate their epigenetic state to adapt to changes in applied stress. Using an auxin-inducible degron system to deplete cellular CBX5/HP1α, Strom et al [ 158 , 159 ] found that loss of CBX5/HP1α results in significant nuclear softening but not the loss of heterochromatin domains, consistent with their persistence when the methyltransferases responsible for synthesizing H3K9me3 are knocked out [ 160 ]. HP1 can dimerize and potentially cross-link chromatin fibers together [ 161 ].…”
Section: Solid and Liquid States Of Chromatin In The Nucleusmentioning
confidence: 99%
“…Chromatin motion can be further restricted within heterochromatin domains by long-range cross-linking of the chromatin fiber by HP1 dimers [ 193 ]. Strom et al demonstrated that HP1 and specifically HP1 dimerization is not required for heterochromatin condensate maintenance but, through its cross-linking function, contributes to the rigidity of the nucleus [ 158 ]. It should be noted that the cross-linking function of HP1 appears to be independent of its ability to phase separate [ 92 ].…”
Section: Solid and Liquid States Of Chromatin In The Nucleusmentioning
confidence: 99%
“…Post-translational modifications (PTMs), for example, differentially mark histone tails to recruit specific histone readers ( Kouzarides, 2007 ; Prakash and Fournier, 2017 ) or to initiate DNA unwrapping ( Bowman and Poirier, 2015 ). Macromolecular complexes that recognize such PTMs can further impact chromatin organization by cross-linking nucleosomes that are megabases apart in sequence ( Rao et al, 2014 ; Strom et al, 2021 ), or by shifting the position of nucleosomes to expose new DNA sites for transcription initiation. Despite continuing progress towards determining the structure of chromatin in cells ( Hsieh et al, 2015 ; Ricci et al, 2015 ; Nozaki et al, 2017 ; Ou et al, 2017 ; Risca et al, 2017 ; Cai et al, 2018 ; Xu et al, 2018 ; Ohno et al, 2019 ; Otterstrom et al, 2019 ; Krietenstein et al, 2020 ; Su et al, 2020 ), the impressive span of length scales involved, from small chemical modifications in the Ångstrom range to whole chromosome rearrangements on the micrometer scale, creates a tremendous challenge for structural biologists and biophysicists.…”
Section: Introductionmentioning
confidence: 99%
“…The centromere is a chromosomal locus epigenetically defined by the presence of the histone H3 variant CENP-A, which plays crucial roles in the assembly and function of the kinetochore and the maintenance of sister chromatid cohesion during cell division [ 138 , 139 ]. Centromeres are flanked by large heterochromatic regions—the pericentromeres—that play an important role in fostering sister chromatid cohesion during mitosis [ 140 , 141 ]. Like telomeres, the megabase-long chromosomal regions harboring (peri)centromeres are comprised of repetitive DNA sequences [ 139 ].…”
Section: The Atrx /Daxx Histone H33 Chaperone In Chromatin Dynamicsmentioning
confidence: 99%